2012
DOI: 10.1007/s00428-012-1208-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of neutrophil gelatinase-associated lipocalin (NGAL) immunoexpression in follicular-patterned lesions of the thyroid gland

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) is a protein which participates in iron trafficking and which is involved in cancerogenesis and cancer progression. Since its over-expression has been documented in thyroid malignancies in comparison to thyroid normal gland, in the present study, we aimed to determine whether the evaluation of NGAL immunoexpression may be of help in the differential diagnosis of follicular-patterned thyroid lesions. Our additional aim was to test the possible interference of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In line with research by Barresiet al [13,14],NGALexpressionappearedto bespecific(100%)forthyroidcarcinomaandrepresentedasensitivemethod(93%)inPTCincomparisontoC.Inaddition,thecontentoffollicularcavities inCalsoshowedoccasionalNGALexpression,while intumorswithfollicularstructure(suchasPTC-FV), it was negative. In conclusion, all these features of NGAL can contribute to differentiating malignant tumorsfrombenignlesions.Itwasnoteworthythat all immunohistochemical procedures were repeated severaltimeswithanendogenousbiotin-freesystem, butthecontentsofbenignthyroidfollicularcavities still occasionally showed NGAL protein expression, whichwaslikelytocauseNGALfalsepositivityinC.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In line with research by Barresiet al [13,14],NGALexpressionappearedto bespecific(100%)forthyroidcarcinomaandrepresentedasensitivemethod(93%)inPTCincomparisontoC.Inaddition,thecontentoffollicularcavities inCalsoshowedoccasionalNGALexpression,while intumorswithfollicularstructure(suchasPTC-FV), it was negative. In conclusion, all these features of NGAL can contribute to differentiating malignant tumorsfrombenignlesions.Itwasnoteworthythat all immunohistochemical procedures were repeated severaltimeswithanendogenousbiotin-freesystem, butthecontentsofbenignthyroidfollicularcavities still occasionally showed NGAL protein expression, whichwaslikelytocauseNGALfalsepositivityinC.…”
Section: Discussionsupporting
confidence: 84%
“…The cells were regarded as positive for these proteins when immunoreactivity was clearly observed in their nuclei, membrane and/orcytoplasm.Stainingofthefollicularcolloidin the absence of staining of the follicular epithelium was considered nonspecific and negative. We used asemi-quantitativescoringmethodforeachimmunohistochemicalmarkerwiththecut-offvaluesbased ondatapublishedpreviously [4,11,[14][15][16][17]andthe clinicalexperienceofthepathologistsinvolved(NapingLiandXiWang).Thepercentageofpositivecells for each section was counted under 5 high power fields,andthemeanvalueofeachcasewasscoredas follows:0,stainingin<10%ofthecells;1,staining in10-25%ofthecells;2,stainingin26-50%ofthe cells; 3, staining in > 50% of the cells. A score of 0 was considered as negative, and scores of 1 to 3 wereconsideredaspositive.…”
Section: Evaluation Of Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no protein expression was detect by IHC (Human Protein Atlas web site). According to mRNA expression data, previous studies showed that NGAL is overexpressed in thyroid cancer [79-81]. …”
Section: Discussionmentioning
confidence: 99%
“…Barresi et al investigated whether or not NGAL immunoexpression using with a primary antibody (Santa Cruz Biotechnology) may be helpful for differential diagnosis of follicular-patterned thyroid lesions [70]. The thyroid tumors included 25 cases of follicular adenomas, 14 of Hürthle cell adenomas, 2 atypical adenomas, 10 minimally invasive follicular carcinomas (5 with capsular invasion only and 5 with both capsular and vascular invasion), 10 widely invasive follicular carcinomas, 3 Hürthle cell follicular carcinomas, and 8 follicular variant papillary carcinomas.…”
Section: Thyroid Cancersmentioning
confidence: 99%